Efektivitas Program Maghrib Mengaji Dalam Mengembangkan Literasi Al-Qur’an Pada Anak-anak di Desa Kwala Gunung - Nurbayeni, Mustika; Sitorus, Ahmad Syukri; Nst, Mhd.Ary Fadhillah; Ritonga, Khoirunnida (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to evaluate the effectiveness of the Maghrib Mengaji Programme in developing children's Qur'anic literacy in Kwala Gunung Village. The programme focuses on fostering the morals of children and adolescents through learning the Qur'an and strengthening the values of Islamic teachings. Using qualitative research methods and a descriptive approach, this study explored the impact of the programme on improving children's Qur'anic literacy and understanding of Islamic teachings. The results showed that the Maghrib Mengaji Programme conducted by KKN Group 47 UINSU contributed and changed the children in Kwala Gunung Village not only in their ability to read the Qur'an, but also in shaping Islamic morals and behaviour among the children of Kwala Gunung Village.